Electrical stress and failure analysis of power semiconductor devices - Chee, Sean Nicholas (Nanyang Technological University, 2022)
Power electronics' importance is expanding in both industry and society. It has the potential to dramatically increase the efficiency of electricity generation systems. They are crucial components of contemporary power electronics, not only for ordinary use, but also for severe environments. The current architecture of power electronics equipment demands substantial redundancy for reliability. Thus, to optimize power density, it is required to first analyze the dependability of power semiconductors to determine a power device's actual operational margin. It is necessary to understand the fundamental principles of semiconductor power devices to fully fulfil this potential. In summary, this report will investigate the I-V characteristic after power cycling test and a Double Pulse Test. FETs made of gallium nitride (GaN) and MOSFET/IGBTs made of silicon (Si) are used. There will be laboratory simulations and experiments. The goal of this study is to analyse the features of degraded power semiconductors, as well as their switching behaviour